1988
DOI: 10.2337/diacare.11.4.345
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Pulse Reappearance Time in Diagnosis of Peripheral Vascular Disease in Diabetes

Abstract: Forty-eight patients (20 diabetic, 28 nondiabetic) with angiographically confirmed peripheral vascular disease (PVD) were examined to discover whether the measurement of pulse reappearance time (PRT) during reactive hyperemia is a more useful method than the measurement of peripheral systolic blood pressure (ankle pressure index; API) for making a specific diagnosis of PVD. Specific diagnosis refers to the degree and localization of occlusive atherosclerosis determined by Doppler ultrasound techniques for both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Out of the 6629 studies, a total of ten observational studies reporting data from 2585 patients with diabetes met the study criteria and were included in the qualitative data synthesis (Table ) . A flow diagram depicting the overall search results is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of the 6629 studies, a total of ten observational studies reporting data from 2585 patients with diabetes met the study criteria and were included in the qualitative data synthesis (Table ) . A flow diagram depicting the overall search results is shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…Criteria for the diagnosis of PAD using CDUS included the following: an increase in peak systolic velocity ≥100% (or defined as >50% stenosis) in four studies , monophasic waveforms in two studies , peak tibial artery velocity ≤10 cm/s in one study and a combination of significant velocity change and loss of reverse flow in a further study . The remaining two studies used DSA as a reference test , both using a cutoff of >50% reduction in vessel diameter to diagnose PAD. No study reported the performance of a test using CTA or MRA as a reference measure of PAD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We excluded PVD by clinical check-up (assessment of claudication, pulse deficit of popliteal or peripheral arteries), by oscillography (resting and hyperemic blood flow) [17], and by Doppler ultrasound (pulse reappearance time). Only if the results of all three of these examinations were normal PVD was excluded.…”
Section: Methodsmentioning
confidence: 99%
“…The examinations were carried out in the same way as the measurement of the pulse reappearance time [17]. Therefore the half-maximum amplitude of the hyperemic ascent was evaluated manually and expressed in percentage of the amplitude of blood flow under resting conditions.…”
Section: Methodsmentioning
confidence: 99%